Use of droplet vitrification for the conservation of Senegalese cassava varieties. 4th International Symposium on Plant Cryopreservation, Oslo, Norway, June 12-15, 2023 - Ndiaye, Aliou; Panis, Bart (2023)
Proceedings of the 4th International Symposium on Plant Cryopreservation, Oslo, Norway, June 12-15, 2023